Lugar e geograficidade: geografias atravessadas no mundo vivido de Tibau (RN) - Raquel Cunha Paiva (2023)
Space is existential. It is intrinsic to the human being’s life experience, which has a deep relationship with the Earth that constitutes its geographicity. Geographicity and place are part of the daily experience of societies that adapt to the circumstances that the situated being shelters, and starts to attribute meanings to certain spaces that constitute identities, memories, histories and places of life. Over time, spaces undergo changes that realign the dynamics and symbolic meanings of places. Spatial phenomena cross the senses and human existence. In Tibau, on the coast of Rio Grande do Norte, an old fishing village, phenomena related to leisure, maritimity and the institutionalization of the urban way of life crossed the existential geography of his lived world. It has the highest index of vocation rentals in the Northeast, which is the ratio between occasional residences and permanent residences. The villeggiature was consolidated from beach houses destined for the leisure of a wealthy population of Mossoró, neighboring municipality. With the growing demand for infrastructure to carry out leisure practices, the village of Tibau was being urbanized, it became municipalized based on the justification of tourist potential and today it faces several dynamics of an urban city, such as gentrification, real estate speculation, environmental degradation, touristification and erasure of the local culture and way of life. In this sense, that instigates the research is: what do the native residents think about these phenomena? What are the places that make up the geographicity of Tibau? Based on the phenomenological method, which seeks to reflect on the relationships of being-in-the-world, semi-structured interviews were carried out with 20 residents of Tibau, who pointed out the various changes in their way of life in a short period of time and the difficulty of maintaining their experiences in formerly shared places. In the intersubjective discoursed of the interviewees, eight places were highlighted: Morros de Areia Colorida, Vertente, Pedra do Chapéu, Praia, Brisa, Centro de Artesanato, Gancho and Igreja Santa Terezinha, which constitute the cartography of places, a potential instrument of social claim and policy to ensure the permanence of the identity and places of life of Tibau’s population. The symbolic places that are part of the imaginary of Tibau’s people, were strongly affected by the phenomena that cross Tibau, causing dissatisfaction on the part of residents due to the problems brought in the practices of leisure in the municipality.